Status Populasi Bulu Babi Tripneustes gratilla di Perairan Desa Liang, Pulau Ambon - Prulley A Uneputty; Jesaja A Pattikawa; Frederick Rijoly (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
Research to study status of sea urchin Tripneustes gratilla was carried out at the coastal waters of Liang Village, Ambon Island on September 2012. Belt transect method with the plot witdh 10m was used in this study.It was found that density of T. gratilla in in the area was 0.0122 ind./m with the highest density occurred at transect 1 i.e. 0.016 ind./m 2 . Estimated potential of T. gratilla was 4760 individuals. Based on the size of 145 individuals sampled, mean diameter of T. gratilla in Cape Matiella was 68.35mm and it was ranging from 58.11 mm to 76.61mm. Those sizes of diameter could be grouped into 2 age groups (cohorts) with the mean size of first and second cohorts were 64.51mm and 72.28mm, respectively. In general, length (diameter) – weight analysis showed that growth pattern of sea urchin in the area was negative allometric in which diameter grown faster than weight with the exception of sea urchin in transects 3 and 4 which showed isometric growth i.e. increasing of diameter was proportional to weight.Keywords: Tripneustes gratilla, density, cohort, length-weight relationship 2 while the lowest occurred at transect 4 i.e. 0.009 ind./m 2